Are Indonesians sensitive to contrastive accentuation below the word level? - van Heuven, Vincent J. (Wacana, Journal of the Humanities of Indonesia, 2009)
It is impossible in Indonesian to express narrow-focus meta-linguistic contrasts on subparts of words (whether meaningless syllables or meaningful morphemes). In English and Dutch this possibility exists, as in I meant coffin not coffer or I said meaningful not meaningless. We predict from this circumstance that Indonesian learners of Dutch will not be sensitive to this type of prosodic contrast marking at the sub-word level. Native Dutch speakers should be able to make functional use of this type of contrast. We conducted an experiment with thirteen Indonesian learners of Dutch with lengths of residence in the Netherlands between 3 weeks and 27 years, and a group of thirteen native Dutch speakers as controls. The results show that the Indonesian learners perform at chance level, and are therefore insensitive to narrow-focus contrasts below the word level. Dutch learners are highly sensitive to these contrasts on average, although three out of thirteen performed at chance level. We argue from these results that Indonesian has no word stress.